School Principals’ Instructional Leadership in Enhancing Learning Quality at Elementary Schools in Balikpapan City - Awaluddin Hidayatulloh; Suyatno Suyatno; Ika Maryani (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The relocation of Indonesia’s capital to Nusantara (IKN) in East Kalimantan places surrounding buffer regions, particularly Balikpapan, in a strategic position to provide primary education services that are adaptive to social change and national development. This study aims to analyze the instructional leadership of elementary school principals in IKN buffer areas from the perspective of an education researcher. Employing a qualitative approach with an exploratory case study design, the research draws on in-depth interviews with a school principal, teachers, a school supervisor, and school committee members, all of whom have extensive experience in primary and secondary education. The findings indicate that ideal instructional leadership encompasses human resource development, academic strengthening, administrative governance, facilities and infrastructure management, and school financing, all supported by integrity, communication, and collaboration. Within the IKN buffer context, leadership demonstrates characteristics of glocal leadership, grounded in local values while remaining responsive to global demands. The study also reveals that leadership practices that remain predominantly administrative require strengthening through the integration of instructional and transformational leadership, enabling educational visions and values to be effectively enacted in classroom practice. Overall, the research underscores the importance of reinforcing contextual and adaptive leadership capacity among school principals to enhance the quality of primary education in IKN buffer regions.